Direct linear measurement of root dentin thickness and dentin volume changes with post space preparation: A cone-beam computed tomography study - Shoeb Yakub Shaikh; Safia Shoeb Shaikh (Wolters Kluwer Medknow Publications, 2018)
Aim: The purpose of the present study was direct linear measurement of dentin thickness and dentin volume changes for post space preparation with cone-beam computed tomography (CBCT). Materials and Methods: Ten maxillary central incisors were scanned, before and after root canal and post space preparation, with Orthophos XG three-dimensional hybrid unit. Thirteen axial section scans of each tooth from orifice to apex and dentin thickness for buccal, lingual, mesial, and distal were measured using proprietary measuring tool and thereafter subjected to statistical analysis. Furthermore, dentin volume was evaluated using ITK-SNAP software. Results: There was statistically significant difference between the dentin thickness in pre- and postinstrumentation (paired t-test) and also between different groups (one-way ANOVA). In the shortest post length of 4.5mm the post space preparation resulted in 2.17% loss of hard tissue volume, where as 11mm longest post length post space preparation resulted in >40% loss of hard tissue volume. Conclusion: CBCT axial section scan for direct measurements of root dentin thickness can be guideline before and after post space preparation for selection of drill length and diameter.